Eriophyoid mites of Taiwan: description of three species of Calacarini from Hueysuen (Acari: Eriophyoidea: Phyllocoptinae) - Huang, Kun-Wei; Wang, Chin-Fah (Zootaxa, 2004)
In this paper, the authors describe and illustrate three species of Calacarini in three genera, including two new genera and three new species, from Hueysuen (in central Taiwan). They are: Quadratum glaberi gen. et sp. nov. (infesting Stauntonia hexaphylla), Taijutarus triangulus gen. et sp. nov. (infesting Pericampylus formosanus) and Jutarus pasanus sp. nov. (infesting Pasania konishii). A key to the genera and species of Calacarini from Hueysuen is provided.